Community voices: the importance of diverse networks in academic mentoring - Deanna, Rocío (2022)
Mentor relationships are crucial to retention, success, and wellbeing of women and underrepresented minority scientists in academia. A network of diverse mentors may support achieving long-term career goals, advancement, and retention of both mentors and mentees, thus enhancing diversity, equity, and inclusion initiatives.